The cult of the lightweight fighter: culture and technology in the U.S. Air Force, 1964-1991 - Hankins, Michael Wayne (Kansas State University, 2018)
In the late 20th and early 21st centuries, military aviation technology grew expensive and politically divisive, and this is not without precedent. In the 1960s and 1970s, the F-15 Eagle and F-16 Falcon represented a controversial shift both in the cost of development and in tactical doctrine for the United States Air Force (USAF), yet the motivating factors that influenced their design are not fully understood. Most of the literature either has focused on a teleological exploration of technical evolution or has held to a “genius inventor” paradigm, lionizing individual engineers and planners. Other works have focused on these aircraft as factors that changed the Air Force's tactical approach to warfighting or have simply evaluated their combat performance. Although these approaches are valuable, they do not account for the effect that institutional culture and historical memory had on the F-15 and F-16 programs. This dissertation argues that the culture of the fighter pilot community was based on a constructed memory of World War I fighter combat, idealizing a heroic, romanticized image of “Knights of the Air.” This fighter pilot community attempted to influence the F-15 and F-16 programs to conform to their vision of an idealized past. Furthermore, a smaller group of these pilots, calling themselves the “Fighter Mafia” (and later the “Reformers”) radicalized these ideas, rejecting the Eagle and Falcon as not representative of their ideal vision. Through public and political activism, this group affected the discourse of military technology from the mid-1970s to the present. Drawing on David Nye’s work on the connections between technology and cultural historical narratives and identity, this work will demonstrate that culture and institutional historical memory can be important factors in driving the development of military technology.
Keywords: Military aircraft; United States Air Force; Military aircraft technology; Fighter pilot culture; Reform movement; F-15 F-16 fighter aircraft